2022
DOI: 10.1002/gch2.202100118
|View full text |Cite
|
Sign up to set email alerts
|

Transparent, Flexible, and Low‐Operating‐Voltage Resistive Switching Memory Based on Al2O3/IZO Multilayer

Abstract: In this study, a different number of indium zinc oxide (IZO) interlayers are fabricated into Al 2 O 3 ‐based transparent resistive switching memory on a transparent indium tin oxide (ITO)/glass substrate at room temperature. Al 2 O 3 /IZO multilayer transparent memory has a transmittance of at least 65% in the wavelength range of 400–900 nm. In addition, the Al 2 O 3 /IZO mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In particular, amorphous oxide semiconductors (AOS), such as IGZO or ZTO, have high flexibility, due to a lack of grain boundaries, which enables low-processing temperatures. This facilitates the use of flexible substrates (paper, polyimide, polyethylene naphthalate (poly(ethylene 2,6-naphthalate) (PEN) / polyethylene terephthalate (PET) [24,83,84], providing the means for embedded flexible technologies in wearables and internet-of-things applications. Furthermore, AOS are used in flat-panel display technology for active-matrix driver circuits, making them ideal candidates for future integrated memristor-based hardware for AI.…”
Section: Oxide Semiconductors Oemsmentioning
confidence: 99%
“…In particular, amorphous oxide semiconductors (AOS), such as IGZO or ZTO, have high flexibility, due to a lack of grain boundaries, which enables low-processing temperatures. This facilitates the use of flexible substrates (paper, polyimide, polyethylene naphthalate (poly(ethylene 2,6-naphthalate) (PEN) / polyethylene terephthalate (PET) [24,83,84], providing the means for embedded flexible technologies in wearables and internet-of-things applications. Furthermore, AOS are used in flat-panel display technology for active-matrix driver circuits, making them ideal candidates for future integrated memristor-based hardware for AI.…”
Section: Oxide Semiconductors Oemsmentioning
confidence: 99%
“…Despite its low (≥10) I ON /I OFF ) ratio, this device has a lower switching voltage than other organic ReRAM devices, but its endurance of only 30 cycles is a drawback for non-volatile memory applications. Future electronic gadgets, on the other hand, appear to be flexible [15], transparent [15,16], and transient [17]. Yalagala et al reported on the rapid (<4 s) dissolving of a ReRAM device with a MgO-PVP-Ge active layer and Ag and ITO electrodes [17].…”
Section: Transport and Memory Studymentioning
confidence: 99%
“…Amorphous oxide semiconductors (AOSs) are an especially interesting class of materials to be employed as photosensitive layers in such devices . First, AOSs have high flexibility and low-processing temperatures, allowing the use of flexible substrates, which is crucial for internet-of-things (IoT) applications. , Additionally, using AOS in optoelectronic memories allows one to benefit from the mature AOS pixel-driver circuit technology employed in commercial flat-panel displays. This holds great promise for a straightforward integration of AOS optoelectronic memories into the neuromorphic system on panel (SoP) technology.…”
Section: Introductionmentioning
confidence: 99%